Video anoscopy: results of routine anal examination during colonoscopies - Gomes, Alexandre; Minata, Maurício Kazuyoshi; Jukemura, José; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2019)
Background and study aims Anal examination and video anoscopy (VA) are rarely performed during colonoscopies. The aim of this study is to demonstrate that anal examination and VA provide important information in all routine colonoscopies. Patients and methods A cross-sectional study was conducted on 12,151 patients screened by VA which were performed during routine outpatient colonoscopy between 2006 and 2018. The aspects studied were: normal examination; hemorrhoidal disease; thrombosed hemorrhoids; anal fissure; perianal Crohn’s Disease; perianal fistula; condyloma; polyps; neoplasms; stenosis; bleeding. Results Of the colonoscopies performed on 12,151 patients, 9,364 cases (77.06 %) presented some alterations. Internal I degree hemorrhoids (5911 – 48.65 %); internal hemorrhoids of II, III and IV degrees (2362 – 19.44 %); thrombosed hemorrhoids (120 – 0.99 %); bleeding (56 – 0.46 %); fissure (415 – 3.42 %); perianal fistula (42 – 0.35 %); perianal Crohn’s Disease (34 – 0.28 %); condylomas (18 – 0.15 %); anal stenosis (30 – 0.25 %); other findings (310 – 2.55 %); polyps (62 – 0.51 %), one of which was adenomatous with high-grade dysplasia; four cases of anal canal neoplasia (0.03 %): two cases of squamous cell carcinoma and two cases of adenocarcinoma. Conclusion The association of routine video anoscopy during colonoscopy improved diagnosis of neoplastic anal lesions, allowed correct classification of the degree of hemorrhoidal disease, helped to confirm the bleeding site and detected other anal pathologies. The main findings were hemorrhoidal diseases, fissures and perianal fistulas. The study suggests that VA should be used in all colonoscopies.